Dendritic cells primed with a chimeric plasmid containing HIV‐1‐gag associated with lysosomal‐associated protein‐1 (LAMP/gag) is a potential therapeutic vaccine against HIV. Issue 8 (19th May 2016) - Lucas, Carolina G. D. O.; Matassoli, Flavio L.; Peçanha, Ligia M. T.; Santillo, Bruna Tereso; Oliveira, Luanda Mara da Silva; Oshiro, Telma Miyuki; Marques, Ernesto T. D. A.; Oxenius, Annette; de Arruda, Luciana B.
ABSTRACT: The decline in number and function of T cells is a hallmark of HIV infection, and preservation or restoration of HIV‐specific cellular immune response is a major goal of AIDS treatment. Dendritic cells (DCs) play a key role in the initiation and maintenance of the immune response, and their use as a vaccine vehicle is a promising strategy for enhancing vaccine efficacy. We evaluated the potential of DC‐mediated immunization with a DNA vaccine consisting of HIV‐1‐p55gag (gag, group‐specific antigen) associated to lysosomal associated protein (LAMP) sequence (LAMP/ gag vaccine). Immunization of mice with mouse DCs transfected with LAMP/gag (Lg‐mDCs) stimulated more potent B‐ and T‐cell responses than naked DNA or DCs pulsed with inactivated HIV. Anti‐Gag antibody levels were sustained for at least 3 mo after immunization, and recall T‐cell responses were also strongly detected at this time point. Human DCs transfected with LAMP/ gag (Lg‐hDCs) were also activated and able to stimulate greater T‐cell response than native gag ‐transfected DCs. Coculture between Lg‐hDCs and T lymphocytes obtained from patients with HIV resulted in upregulation of CD38, CD69, HLA‐DR, and granzyme B by CD4 + and CD8 + T cells, and increased IFN‐γ and TNF‐α production. These results indicate that the use of LAMP/ gag ‐DC may be an efficient strategy for enhancing immune function in patients with HIV.—Lucas, C. G. D. O., Matassoli, F. L., Peçanha, L. M. T., Santillo, B. T., Oliveira, L. M. D. S., Oshiro, T. M., Marques, E. T. D. A., Jr., Oxenius, A., de Arruda, L. B. Dendritic cells primed with a chimeric plasmid containing HIV‐1‐gag associated with lysosomal‐associated protein‐1 (LAMP/ gag ) is a potential therapeutic vaccine against HIV. FASEB J. 30, 2970‐2984 (2016). www.fasebj.org